2010
DOI: 10.1590/s1806-83242010000400011
|View full text |Cite
|
Sign up to set email alerts
|

Metallographic analysis of the internal microstructure of orthodontic mini-implants

Abstract: Effective orthodontic anchorage may be obtained by miniimplants inserted into the maxillary bones. However, the risk of miniimplant failure is one of the most important issues, especially the rupture of its structure referred to as fracture, mainly due to metal deficiencies. This study analyzed the internal microstructure of orthodontic mini-implants, ascertaining the composition of the metal to detect possible discontinuities from the surface to the core of the screws. Eighteen samples of mini-implants, of 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
1
11
0
4
Order By: Relevance
“…14,23 According to the manufacturers, Neodent miniimplants are rated at grade 5 Ti6Al4V in their chemical composition (ASTM-136), while the Morelli mini-implants rate grade 23 Ti6Al4V (ASTM-136). In the present study, chemical analysis showed that heavy metals were present in both brands of mini-implants, Previous studies have shown that osteoblasts proliferate on the alloys studied 11,15,24 and that the mini-implants used for temporary anchorage in orthodontics may partially osseointegrate. 19,20 Also, both implant and thread design may influence insertion and removal torques, highlighting the importance of selecting an adequate design according to cortical bone thickness.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…14,23 According to the manufacturers, Neodent miniimplants are rated at grade 5 Ti6Al4V in their chemical composition (ASTM-136), while the Morelli mini-implants rate grade 23 Ti6Al4V (ASTM-136). In the present study, chemical analysis showed that heavy metals were present in both brands of mini-implants, Previous studies have shown that osteoblasts proliferate on the alloys studied 11,15,24 and that the mini-implants used for temporary anchorage in orthodontics may partially osseointegrate. 19,20 Also, both implant and thread design may influence insertion and removal torques, highlighting the importance of selecting an adequate design according to cortical bone thickness.…”
Section: Discussionsupporting
confidence: 57%
“…This titanium alloy, known as grade 5 Ti, confers higher fatigue resistance than does cp Ti, yet maintains properties such as resistance to corrosion and low toxicity. 11,14,15 The chemical and topographic features of miniimplant surfaces are regarded as important in terms of their interface with bone cells because of their high quality of osseointegration, 13 since osteoblast morphology can be influenced by composition and type of surface treatment. 16 If corrosion sets in because of the chemical composition of the alloy, encapsulated tissue may be formed secondarily to the release of metallic ions and other byproducts of corrosion, as well as ionic contamination of organic tissues, thus compromising cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the proportion of titanium was similar in all commercial brands, titanium alloys can have different amounts of alpha-phase and beta-phase titanium, possibly due to differences in the manufacturing process of the alloy. For instance, Cotrim-Ferreira et al (2010) 11 showed that there were quantitative differences in alpha-phase and beta-phase titanium in mini-implant alloys from three commercial brands (SIN, Dewimed, and CON), even though they were within the guidelines of the "Technical Committee of European Titanium Producers" described in Publication ETTC-2.…”
Section: Discussionmentioning
confidence: 99%
“…To meet these requirements, the titanium alloy (Ti-6Al-4V) chosen for manufacture of mini-implants incorporates aluminum (Al) and vanadium (V) into its composition along with commercially pure titanium (cpTi) 10 . Ti-6Al-4V alloy has higher fatigue resistance than (cpTi), while having the same corrosion resistance and low toxicity 11 . The amount of each component in the alloy, in addition to the manufacturing quality, can alter its mechanical properties such as hardness and resiliency, which are responsible for the fracture resistance of the mini-implant.…”
Section: Introductionmentioning
confidence: 99%
“…They can be manufactured using several materials, including commercially pure titanium (Ti cp), titanium alloy (Ti-6Al-4V) and stainless steel [3,4]. In terms of features, these materials should be non-toxic, biocompatible, present favorable mechanical properties, be able to withstand stress, deformation and corrosion [5,6], and not induce adverse local or biological responses [7,8]. In this respect, these devices should not exhibit surface degradation over time, so as to ensure very low or no-ion release and good corrosion resistance [6,9].…”
Section: Introductionmentioning
confidence: 99%